2009
DOI: 10.1007/s00234-009-0529-4
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up assessment of vestibular schwannomas: volume quantification versus two-dimensional measurements

Abstract: Introduction A conservative treatment strategy is often proposed as a primary treatment option in the management of vestibular schwannomas (VS). In this "wait and scan" policy, audiovestibular symptoms are monitored regularly, and VS growth is measured on consecutive magnetic resonance images (MRI). The aim of this study is validation of two-dimensional versus volume MRI assessment in the longitudinal follow-up of VS and to define tumor growth beyond measurement error. Methods MRI scans of 68 consecutive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
122
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 25 publications
(46 reference statements)
11
122
1
Order By: Relevance
“…Compared to Fig. 1, the net displacement field in (b) does not indicate a volume change shown for vestibular schwannomas [15], while for glioblastomas, any significant difference has not been shown between volumes measured on 2D and 3D scans [16]. Tumor volume change (objective response) is an important endpoint in clinical trials [17].…”
Section: Discussionmentioning
confidence: 97%
“…Compared to Fig. 1, the net displacement field in (b) does not indicate a volume change shown for vestibular schwannomas [15], while for glioblastomas, any significant difference has not been shown between volumes measured on 2D and 3D scans [16]. Tumor volume change (objective response) is an important endpoint in clinical trials [17].…”
Section: Discussionmentioning
confidence: 97%
“…Vestibular schwannoma growth can be demonstrated by volumetric studies or diameter measurements (2,15). Studies in the literature have shown that diameter measurements can be used instead of volumetric measurements to compare tumor size (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the imaging technique used in the conservative management of vestibular schwannomas (2,3). T1W sequences with a gadolinium-based contrast agent are the gold standard for the initial detection and follow-up examinations of these tumors (5, 7).…”
Section: Discussionmentioning
confidence: 99%
“…This has been suggested to increase accuracy and inter-rater reliability. A study by van de Langenberg et al [5] considered 68 patients with vestibular schwannomas and compared growth using both two-dimensional and volumetric MRI measurements and found that interobserver error using bi-dimensional measurements was more than twice the volumetric inter-observer error rate. A randomized control trial for motexafin in brain metastasis in which tumor response rates were analyzed using different measurements found a 50 % reduction of tumor using bi-dimensional measures versus a 65 % reduction of tumor using volumetric measures [6].…”
Section: Anatomic Imaging Sequencesmentioning
confidence: 98%